2009
DOI: 10.1111/j.1528-1167.2008.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine–valproic acid combination therapy for medically refractory epilepsy

Abstract: Summary Purpose:  A retrospective study of lamotrigine (LTG)–valproic acid (VPA) combination therapy in medically refractory epilepsy. Methods:  Patients were identified with an adult epilepsy clinic database and were included if they had been on LTG–VPA combination therapy for at least 6 months. Patient demographics and information about epilepsy type, severity, and degree of medical intractability were obtained by retrospective chart review. The primary outcome measure was change in baseline seizure frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
1
24
0
6
Order By: Relevance
“…The dose of lamotrigine should be carefully titrated and reduced in patients on therapy with valproate, resulting in avoiding problems with toxicity and many adverse events of lamotrigine. Several studies have shown that this drug combination have a potentially sinergistic effect on refractory epilepsy [54][55][56]. Furthermore, other authors reported a significant decrease in lamotrigine clearance caused by concomitant administration of valproate, as it was confirmed in our study [43][44][45].…”
Section: Lamotriginesupporting
confidence: 77%
“…The dose of lamotrigine should be carefully titrated and reduced in patients on therapy with valproate, resulting in avoiding problems with toxicity and many adverse events of lamotrigine. Several studies have shown that this drug combination have a potentially sinergistic effect on refractory epilepsy [54][55][56]. Furthermore, other authors reported a significant decrease in lamotrigine clearance caused by concomitant administration of valproate, as it was confirmed in our study [43][44][45].…”
Section: Lamotriginesupporting
confidence: 77%
“…Lamotrigine is a novel broad‐spectrum AED widely used in the treatment of epilepsy such as partial, secondarily generalized, and tonic‐clonic seizures (Messenheimer, ; Moeller, Rahey, & Sadler, ; Warshavsky, Eilam, & Gilad, ). For electrical kindling, as far as we know there was a study to observe the antiepileptogenic activity of LTG with a dose of 20 mg/kg in rats, and it proved LTG can delay the development of kindling, but cannot further stop the kindling acquisition after a washout phase (Stratton, Large, Cox, Davies, & Hagan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative seizure freedom is associated not only with completeness of surgical resection but also with the postoperative medication regimen (Moeller et al, 2009). Medication is crucial after surgery, particularly the combination and doses of AEDs (Moeller et al, 2009). Adherence to AED therapy is critical for effective epilepsy management (Faught, 2012), and nonadherence may be the most important cause of poorly controlled epilepsy (Manjunath et al, 2009).…”
mentioning
confidence: 99%